Sistem Informasi Penjualan Obat Berbasis Web Pada Apotek Khodijah - Rohili Rohili; Eko Setia Budi (STMIK Budi Darma, 2022)
Khodijah Pharmacy is one of the business organizations or corporate agencies engaged in the pharmaceutical sector that sells medicines, both prescription and over-the-counter drugs. The operational activities carried out at the Khodijah Pharmacy are still carried out conventionally, which consist of recording sales, recording drug purchases to suppliers, recording drug stocks, recording pharmacy revenues and making reports that are still written on a piece of paper. Operations carried out conventionally often have problems such as torn paper, errors in recording sales, recording drug purchases to suppliers, recording drug stocks, recording pharmacy revenues, and errors in reporting so that the owner does not get valid information and can result in losses to consumers. Khodijah Pharmacy. From the problems faced can be solved by building a web-based drug sales information system. The purpose of making this web-based drug sales information system is to provide convenience in carrying out operational activities at Khodijah Pharmacy. The method that the author uses in making this web-based drug sales information system is to use the prototype method, while making this website the author uses the CodeIgniter Framework and also Boostrap. For testing the author's website using Black Box Testing. The resulting drug sales information system provides convenience in carrying out operational activities at Khodijah Pharmacy.